Strategi Peningkatan Pertumbuhan Ekonomi Brunei Darussalam dalam Menghadapi Ketergantungan Sumber Daya Alamnya - Dhia Alya Shoffa; Muhammad Fauzan Ramadhan; Muhammad Fitrah Fuzan; Rafi Ilhamdi Almasyuri Nurdiansyah; Rizky Aditya Aulia (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
Brunei Darussalam is known as a country with abundant natural resources, especially petroleum and natural gas, which form the backbone of its economy. However, the heavy reliance on the energy sector makes the country vulnerable to changes in oil prices in the global market. This research aims to examine natural resource management strategies that can promote economic diversification and ensure long-term sustainability. The research used a qualitative descriptive method with data drawn from official reports, scientific articles, and international organizations. The results show that economic diversification in the tourism, agriculture, and technology sectors, as well as oil revenue management can be the key to building a more stable economy in Brunei.